Strategi Pemasaran UMKM dalam Menghadapi Pasar di Era Pandemi Covid 19 - Kuswinton (Jurnal Ekonomi & Bisnis, 2022)
The increasingly rapid economic development in Indonesia makes competition between businesses increasingly tight. The Covid-19 pandemic has an impact on UMKM entrepreneurs which can be viewed from the supply and demand point of view. The purpose of the study was to determine the marketing strategy of MSME in Facing the Market in the Covid 19 Pandemic era. The type of research used was descriptive research. Descriptive research is conducted so that researchers can better describe the properties that are known to exist that are relevant to the variables studied. Descriptive method is an analytical method by first collecting existing data and then clarifying, analyzing, then interpreting so that it can provide a clear picture of the situation under study. The results of research conducted face-to-face with MSME business actors, that the marketing strategy used today is to do online sales and add various kinds of food, add to the taste of food and choose other locations in making sales to increase daily income and be able to anticipate MSME competition in Covid-19 era.